Efficacy and safety of panchgavya GHRIT along with flunarizine in prophylaxis for migraine patients: a comparitive study - Trivedi, Mohit; Dixit, Vishal; Mahmood, Syed Esam; Mishra, Sunil Kumar; Keshari, S. S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Propranolol and flunarizine have proven to be useful tools in migraine prophylaxis. This trial aims the comparison of the efficacy of flunarizine, flunarizine and placebo and flunarizine and panchgavya ghrit in migraine prophylaxis. Methods: The present study was a prospective, randomized, open-label, blinded-endpoint trial. Patients with chronic migraine were randomized (1:1:1) to flunarizine and flunarizine and placebo and flunarizine and panchgavya ghrit in three treatment groups. The study was carried out in outdoor patients in the department of Psychiatry, T.S. Mishra Medical College and Hospital, Lucknow and K.G.M.U, Ayush Department, Lucknow after clearance from Institutional Ethical Committee. Data was analysed using SPSS software. Results: The prevalence of migraine was found to be higher in the age group greater than 30 years and females. Overall there was more reduction in CGI scores in flunarizine with panchgavya ghrit and the other two groups equally at the end of 4, 6 8 and 10 weeks. Decrease in MIDAS score was observed after the therapy. Clinical Global Impression rating scale employed revealed that to start with subjects scored 7 which stands for pathology interfering in many life functions which reduced drastically in Group C as compared to Group B and Group A in descending order. Pain scales namely VAS (visual analogue scale), NPRS (Numeric Pain Rating Scale), VRS (verbal rating scale) when employed denoted there was decreased migraine frequency, decreased perception of pain, less intake of abortive medication consumed by subjects implying there were reduction in number of migraine days and there was decrease in the abortive medications taken for the same. Group C scored better on pain scales followed by Group B and Group A. Lower proportion of individuals in group C had Behavioural Toxicity and Neurological Side effects as compared to Group A and B. Conclusions: Panch gavya ghrit when administered along with flunarizine was more efficacious and safe when compared with other two groups. However large multicentric RCTs of long duration and involving more number of subjects are required to ascertain these facts.